Estimated human capital externalities in an endogenous growth framework - Jim Malley; Ulrich Woitek (Center for Economic Studies and ifo Institute (CESifo), 2019)
To better understand the quantitative implications of human capital externalities at the aggregate level, we estimate a two-sector endogenous growth model with knowledge spill-overs. To achieve this, we account for trend growth in a model consistent fashion and employ a Markov-chain Monte-Carlo (MCMC) algorithm to estimate the model's posterior parameter distributions. Using U.S. quarterly data from 1964-2017, we find significant positive externalities to aggregate human capital. Our analysis further shows that eliminating this market failure leads to sizeable increases in education-time, endogenous growth and aggregate welfare.
Keywords: C11; C52; E32; 330; human capital externalities; endogenous growth; Bayesian estimation